(untitled) (IUBAT Review, 2026)
A novel mixed-ligand copper(II) complex, [Cu(Asp)(bpy)]·nH₂O, incorporating aspartic acid (Asp) and 4,4′-bipyridine (bpy), was synthesized and extensively characterized to elucidate its redox, magnetic, thermal, and spectroscopic properties. Fourier-transform infrared spectra confirmed coordination through the carboxylate oxygen of Asp and the nitrogen atoms of bpy, forming a mixed N,O-donor environment around the Cu(II) center. UV–Visible spectroscopy revealed d–d and metal-to-ligand charge transfer transitions, while fluorescence spectra displayed emission quenching due to the paramagnetic Cu(II) ion, confirming effective metal–ligand interaction. The complex exhibited an effective magnetic moment (μeff) of 2.46 Bohr magnetons, consistent with a single unpaired electron in a distorted octahedral geometry. Thermogravimetric analysis indicated a multi-step decomposition pattern with stability up to 350 °C, suggesting strong metal–ligand coordination and potential thermal robustness. Electrochemical investigations using cyclic voltammetry demonstrated a quasi-reversible Cu(II)/Cu(I) redox couple, with diffusion-controlled kinetics and ligand-induced stabilization of the Cu(I) oxidation state. Molar conductivity measurements indicated the formation of a neutral complex, further confirming complete coordination. Collectively, these findings establish the structural integrity and multifunctional nature of the Cu–Asp–bpy complex. Owing to its redox reversibility, paramagnetic character, and high thermal stability, the complex shows promise for applications in electrocatalysis, redox-active materials, and bioinspired electron-transfer systems. This study provides valuable insight into how synergistic N,O-ligand coordination can modulate copper redox chemistry and enhance functional stability for potential catalytic and electronic applications. These findings collectively demonstrate that the Cu–Asp–bpy complex possesses a stable Cu(II)/Cu(I) redox couple and high thermal durability, making it a promising candidate for electrocatalytic and bioinspired electron-transfer applications. IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 82-104